Investigating Preschool Children’s Metapragmatic Awareness Development Through Force-Dynamics Model - Lulu Cheng; Xiaomeng Xue; Haoran Mao; Yang Gao; Jianxin Zhang; Yanqin Liu (SAGE Open)
This study investigates the development of metapragmatic awareness in preschool children through the lens of Talmy’s Force-Dynamics Model. Using conversation data from 60 Mandarin-speaking children aged 4 to 6, obtained from the International Child Language Data Exchange System (CHILDES), the research employs a custom coding framework to analyze how children’s interactions reflect seven core force-schemata. These schemata are examined in relation to the three dimensions of metapragmatic awareness: metacognitive, metarepresentational, and metacommunicative awareness. Quantitative and qualitative analyses, conducted with AntConc and SPSS 25.0, reveal developmental patterns, correlations, and age-related differences in schema usage and awareness levels. The findings demonstrate: (1) a progression from egocentric to socially responsive communication, reflected in children’s evolving use of force-schemata; (2) distinct developmental trajectories across the three awareness dimensions, with metacognitive and metacommunicative skills showing significant age-related improvements, while metarepresentational awareness develops more gradually; and (3) strong positive correlations between force-schema usage and metapragmatic awareness, suggesting that as children learn to monitor and adjust their language, they also become more skilled at using specific language strategies (force-schemata) in different social situations. These findings illustrate how children’s pragmatic skills grow with age, particularly in their ability to adapt language use to fit the social context. The study also provides practical recommendations for educators, speech therapists, and parents, highlighting how targeted interventions can foster children’s communicative competence.